Meningkatkan Motivasi Belajar Al-Qur’an Bagi Anak-Anak Dalam Program Magrib Mengaji Di Desa Batu Tambun - Agus Ardiansyah Halomoan Ritonga; M.Wahyudi; Khoirul Bustan; Ade Angriani Nst; Rahmadani Nst; Rahmi Malini; Rizki Adelina; Pitru Juwita Lubis; Nur Hamni (Jurnal Pengabdian Masyarakat Nusantara, 2024)
Reciting the Qur’an is the activity of reading the Al-Qur’an, which has been one of the main forms of worship since the beginning of the development of Islam in the archipelago. Maghrib recitation is one of the programs to cultivate reading the Al-Qur’an after carrying out the evening prayer for children in Batu Tambun Village. This is also in accordance with the Real Work Lecture work program from group 43, namely Maghrib reciting the Al-Qur’an. The culture of reading the Qur’an has recently disappeared in Batu Tambun Village. One of the causes is the influence of the very rapid development of information technology. Children are more interested in watching television and using cellphones than reading the Al-Qur’an. This activity carried out by STAIN MADINA Community Service Students group 43 is to increase or regrow interest in reading the Qur'an after the evening prayer for children. With this program, it is hoped that the children of Batu Tambun Village can take advantage of the time to get closer to the creator, namely Allah SWT